The huntsman : winter's war [videorecording (DVD)] - Hemsworth, Chris; Theron, Charlize; Blunt, Emily; Frost, Nick, 1970- (Universal Studios, 2016)
As a war between rival queen sisters Ravenna and Freya escalates, Eric and fellow warrior Sara, members of the Huntsmen army raised to protect Freya, try to conceal their forbidden love as they combat Ravenna's wicked intentions.